Listeria monocytogenes-associated endovascular infections: A study of 71 consecutive cases. Issue 4 (October 2019) - Shoai-Tehrani, Michka; Pilmis, Benoit; Maury, Mylène M.; Robineau, Olivier; Disson, Olivier; Jouvion, Gregory; Coulpier, Gabrielle; Thouvenot, Pierre; Bracq-Dieye, Hélène; Valès, Guillaume; Leclercq, Alexandre; Lecuit, Marc; et al.
Highlights: Endovascular listeriosis is a rare but severe form of invasive listeriosis. It is mostly reported in older patients with prosthetic devices. Listeriosis endocarditis is associated with a 41% mortality. Summary: Background: Listeria monocytogenes -associated endovascular infections are not well characterized. Methods: Retrospective study of 71 culture-proven cases reported to the French National Reference Center for Listeria from 1993 to 2018. Results: Seventy-one cases were identified: 42 with vascular aneurysms/prosthetic infections, 27 with endocarditis, 2 with both. Fifty-eight were men (82%); median age was 75 years [46–92]; 93% reported co-morbidities (66/71), including 50% with immunosuppressive conditions. Vascular infections consisted of infected aneurysms (68%) or prosthetic graft infections (32%); vascular rupture was reported in 25/42 (60%). Tissue samples grew L. monocytogenes in 98% (43/44) and blood cultures in 64% (27/42). Endocarditis cases involved prosthetic or native valves or intracardiac devices in respectively 62% (18/29), 28% (8/29) and 10% (3/29). Infected valves were aortic (62%, 16/26), mitral (31%, 8/26) or both (8%, 2/26); 38% patients required surgery; 45% displayed heart failure; 17% had concomitant neurolisteriosis. In-hospital mortality in vascular infections was 12% (5/42) and 41% (12/29) for Lm -associated endocarditis. Conclusions: Endovascular listeriosis is a rare but severe infection. It manifests as vascular infections and endocarditis, mostly in older patients with vascular or cardiac valve prosthetic devices and co-morbidities. Mortality in Lm -associated endocarditis is twice higher than with other pathogens, requiring prompt recognition and treatment.